Law Enforcement of Paper Rupiah Mutilation Practice from the Perspective of Law Number 7 of 2011 Concerning Currency and Jarimah Ta’zir - Al Munawar, Faishal Agil; Wiria Tarita, Yuanggi Nur (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
Research Objective: This study examines law enforcement measures against rupiah bill mutilation by Bank Indonesia’s Malang office, analyzing legal frameworks and enforcement strategies. Research Method: The study employs an empirical juridical approach with a sociological emphasis on law. Data were collected through interviews, document analysis, and a literature review. Results: Bank Indonesia Malang implements public education, awareness initiatives, formal warnings, and inter-agency collaboration to address currency mutilation. Findings and Implications: Currency mutilation violates Law No. 7/2011 on Currency and Islamic law principles. Offenders face imprisonment, fines, and other sanctions reflecting the economic significance of currency protection. Conclusion: Indonesia maintains a comprehensive legal framework against currency mutilation. Bank Indonesia Malang actively enforces these regulations through preventive and punitive measures within national and Islamic legal structures. Contribution: This research documents practical enforcement strategies, examines regulatory implementation at regional levels, highlights Islamic legal principles, and provides a reference for comparative studies. Limitations and Suggestions: Geographic focus on Malang limits generalization. Future research should compare multiple regions, measure awareness campaign effectiveness, explore technological solutions, examine cross-jurisdictional enforcement, and assess public compliance with currency protection regulations.